Simpsons world the ultimate episode guide, seasons 1-20 - Groening, Matt 1954- (Harper, 2010)
"Comprehensive episode synopses for 20 seasons of The Simpsons, including 128 new gut-busting episodes never before covered! Stuff you may have missed! More screen shots than ever before! Over four hundred character profiles! Every chalkboard phrase Bart has ever written! Nifty new art throughout! Quotes and quips from all your favorite characters! Two or more jam-packed pages devoted to every episode!"
Keywords: The Simpsons -- Fernsehsendung; Simpsons (Television program)